Inside the New Mexico Senate : Boots, Suits, and Citizens. - Feldman, Dede (University of New Mexico Press, 2014)
"Completely honest and highly informative. To look at a legislative body is to observe democracy in the raw-with all its diverse characters and influences and its many conflicts, compromises, and achievements. Dede Feldman, a first-rate observer and chronicler, shows us the insides of the New Mexico State Senate."--Fred Harris, former U.S. Senator and professor emeritus of political science, University of New Mexico Elected to New Mexico's state senate in 1996, Dede Feldman faced the challenges that confront state legislators around the country along with some that are uniquely New Mexican. I.